Systemic sclerosis - Ahathya R; Deepalakshmi D; Emmadi Pamela (Wolters Kluwer Medknow Publications, 2007)
Systemic sclerosis (scleroderma) is a rare generalized disorder of connective tissue origin. This condition is predominantly a clinical diagnosis, based on the clinical signs and symptoms. Here is a case report of 26-year-old female patient with the classical features of this disease. This case is reported for its rarity and variable expressivity. This article also reviews the literature of this uncommon condition.